Strategy for Empowering Community Leaders Towards Prevention Stunting in Souluwe Village, Dolo Main Health Center Working Area, Sigi District - Mahendra, Yusril Isa; Salham, Munir; Anzar, Mohammad (Jurnal Riset Kualitatif dan Promosi Kesehatan, 2025)
Stunting is a condition where toddlers have less length or height compared to their age peers. Chronic nutritional problems are a cause of stunting which is influenced by various factors including socio-economic conditions, maternal nutrition during pregnancy, pain in babies, and lack of nutritional intake in babies so that in the future they may experience difficulty achieving optimal physical and cognitive development. This research aims to find out the strategies of community leaders in empowering Stunting prevention in Souluwe Village, the working area of ​​the Dolo Main Health Center, Sigi Regency. This research method is descriptive qualitative. This research was carried out for one month from April - May 2024. The informants in this research used a purposive sampling technique consisting of Village Heads, Village Midwives, PKK Chairmen, Traditional Leaders. Based on the results of research on the Empowerment Strategy for Community Figures in Handling Stunting in Souluwe Village, Dolo Public Health Center Working Area, Sigi Regency, the government's efforts in responding to Stunting handling are by carrying out several Stunting programs such as posyandu for toddlers, pregnant women, childbearing age, PMT, socialization, and management of nutritional gardens. The conclusion of this research is that the empowerment of community leaders in handling stunting in Souluwe Village has been carried out but is not going well. It is hoped that the government can continue to increase assistance, for all community leaders to support activities to reduce stunting rates and for the community to be proactive in helping to overcome stunting in Souluwe Village.